Chemotherapy Regimens Received by Women With BRCA1/2 Pathogenic Variants for Early Stage Breast Cancer Treatment. Issue 4 (20th June 2022) - Kurian, Allison W; Abrahamse, Paul; Hamilton, Ann S; Caswell-Jin, Jennifer L; Gomez, Scarlett L; Hofer, Timothy J; Ward, Kevin C; Katz, Steven J
Abstract: Background: Genetic testing is widespread among breast cancer patients; however, no guideline recommends using germline genetic testing results to select a chemotherapy regimen. It is unknown whether breast cancer patients who carry pathogenic variants (PVs) in BRCA1 and/or 2 ( BRCA1/2 ) or other cancer-associated genes receive different chemotherapy regimens than noncarriers. Methods: We linked Surveillance, Epidemiology, and End Results registry records from Georgia and California to germline genetic testing results from 4 clinical laboratories. Patients who 1) had stages I-III breast cancer, either hormone receptor (HR) positive and HER2 negative or triple negative (TNBC), diagnosed in 2013-2017; 2) received chemotherapy; and 3) were linked to genetic results were included. Chemotherapy details were extracted from Surveillance, Epidemiology, and End Results text fields completed by registrars. We examined whether PV carriers received more intensive regimens (HR-positive, HER2-negative: ≥3 drugs including an anthracycline; TNBC: ≥4 drugs including an anthracycline and platinum) and/or less standard breast cancer agents (a platinum). All statistical tests were 2-sided. Results: Among 2293 patients, 1451 had HR-positive, HER2-negative disease, and 842 had TNBC. On multivariable analysis of women with HR-positive, HER2-negative disease, receipt of a more intensive chemotherapy regimen varied statistically significantly by genetic results ( P = .02), with platinum receipt more common among BRCA1/2 PV carriers (odds ratio = 2.44, 95% confidence interval = 1.36 to 4.38; P < .001). Among women with TNBC, chemotherapy agents did not vary significantly by genetic results. Conclusion: BRCA1/2 PV carriers with HR-positive, HER2-negative breast cancer had twofold higher odds than noncarriers of receiving a platinum, as part of a more intensive chemotherapy regimen. This likely represents overtreatment and emphasizes the need to monitor how genetic testing results are managed in oncology practice.